2022
DOI: 10.3340/jkns.2021.0034
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical Management of Metopic Synostosis : A Retrospective Study of 18 Cases

Abstract: Objective : To describe the surgical management and postoperative outcomes in infants with metopic synostosis. Methods : We conducted a 5 years retrospective chart review of patients who underwent surgical correction of metopic synostosis at two university hospitals in Egypt during the period between June 2014 and June 2019. The study is conducted to 18 children. The type of surgical procedures and postoperative outcomes were assessed in all patients. Results : Five cases (27.8%) underwent endoscopic-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…31,32 A major limitation of implementing standardized protocols is the lack of objective quantification of severity. The Whitaker classification has been the accepted standard for aesthetic outcomes reporting in craniosynostosis research, [33][34][35][36] but has been shown to have low interrater reliability and cannot predict the need for future interventions. 37 Most often, the decision is subjective and relies on surgical experience.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 A major limitation of implementing standardized protocols is the lack of objective quantification of severity. The Whitaker classification has been the accepted standard for aesthetic outcomes reporting in craniosynostosis research, [33][34][35][36] but has been shown to have low interrater reliability and cannot predict the need for future interventions. 37 Most often, the decision is subjective and relies on surgical experience.…”
Section: Discussionmentioning
confidence: 99%